Learning Video Based on Local Wisdom Aci Tabuh Rah Pengangon Cultural Diversity Material in Indonesia Pancasila Education Content Class V Elementary School - I Made Riandi Saputra; Anak Agung Gede Agung; I Gede Astawan (Jurnal Pendidikan Multikultural Indonesia, 2025)
The Lack of utilization of learning media results in low student learning outcomes in Pancasila Education content. This study aims to determine the quality of design, feasibility and effectiveness of local wisdom-based learning videos in Pancasila Education content on student learning outcomes. Development research uses the ADDIE model involving fifth grade elementary school students and experts as research subjects. The data collection method in this study uses a questionnaire method and multiple-choice tests with quantitative descriptive data analysis techniques and inferential statistics. The results of this study in the form of design, feasibility of local wisdom-based learning videos have been declared suitable for use in Pancasila Education learning and the effectiveness of learning videos conducted through a one-sample t-test obtained a tvalue of 13.217> ttable 1.694 so that H0 is rejected and H1 is accepted. It can be concluded that local wisdom-based learning videos of the aci tabuh rah pengangon tradition are effectively applied to the cultural diversity material of the Pancasila Education content of fifth grade at SD Negeri 1 Penatih.